Measurement of Complex Formation Process of Lead (II) with Fulvic Acids at pH= 8 - Makharadze, Tamar (Current Topics on Chemistry and Biochemistry Vol. 1, 2022)
The present work aims to investigate the complex formation process between the pure samples of FA, isolated from natural waters and Pb and to calculate the average stability constant of lead fulvate complex. Complex formation process between Pb (II) and fulvic acids was studied by the solubility method at pH=8.0. The suspension of Pb(OH)2 was used as a solid phase. Fulvic acids were isolated from Paravani lake by the adsorption–chromatographic method. During the calculation of molar concentrations of fulvic acids, was taking into consideration the value of average molecular weight of fulvic acids at pH=8 (Mw=6260). It was established, that in the Pb(OH)2(solid) —Pb(II)(solution) —FA—H2O system at pH=8.0,dominates the lead dihydroxy fulvate complex with the structure 1:1,which average stability constant \(β\)(Pb(OH)2FA) = 9,63x106 , lg \(β\)=6,98.